2017
DOI: 10.1002/alr.22020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical outcomes between patients with unilateral and bilateral chronic rhinosinusitis

Abstract: Background Although the majority of patients with chronic rhinosinusitis without nasal polyposis (CRSsNP) suffer from bilateral disease, a subset suffer from unilateral disease. Currently, outcomes following endoscopic sinus surgery (ESS) for medically recalcitrant CRS are inferred from outcomes for patients with bilateral disease. This study compares outcomes of ESS between patients with unilateral and bilateral disease. Methods Patients with CRSsNP who failed appropriate medical therapy and elected ESS wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…Future investigations are needed to verify long-term rhinologic manifestations. Still another is we did not analyze influencing factors (e.g., laterality Beswick et al (2017), surgical extent Ayoub et al (2019), comorbid rhinitis, and concomitant surgical procedures, etc) in the current study. Considering their probable impacts on VAS rating and SNOT-22 scores, future studies are warranted to test their significance in the framework of EPLAs.…”
Section: Discussionmentioning
confidence: 98%
“…Future investigations are needed to verify long-term rhinologic manifestations. Still another is we did not analyze influencing factors (e.g., laterality Beswick et al (2017), surgical extent Ayoub et al (2019), comorbid rhinitis, and concomitant surgical procedures, etc) in the current study. Considering their probable impacts on VAS rating and SNOT-22 scores, future studies are warranted to test their significance in the framework of EPLAs.…”
Section: Discussionmentioning
confidence: 98%
“…This is much higher than previous studies in which only 2.5% to 23.1% of patients with sinus imaging have unilateral disease. [7][8][9] This difference is likely attributable to a couple of different factors. First, the patients in our dataset were all seen in a tertiary rhinology practice.…”
Section: Discussionmentioning
confidence: 99%
“…Published data suggest that the incidence of unilateral sinus involvement ranges from 2.5% to 23.1% of patients undergoing sinus imaging. [7][8][9] A few studies have been published to date attempting to explore the differences in diagnoses in patients with bilateral versus unilateral disease, however many of these studies are small and have focused primarily on inflammatory diagnoses, without delineating the prevalence of neoplasms in each group. The most common diagnoses of patients presenting with unilateral disease are neoplastic disease (benign or malignant), antrochoanal polyp, and allergic fungal sinusitis.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, only weak correlations between SNOT-22 total scores and objective CRS parameters, i.e., endonasal polyp scores [ 8 10 ] or computed tomography (CT) scores [ 11 ], have been observed [ 12 18 ]. In addition, recent meta-analyses suggested that patient-specific factors may also affect the degree of SNOT-22 change after treatment [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%